Dose determination of VV116 in COVID-19 patients with severe liver dysfunction: a case report - Yang, Jing; Jiang, Wenwen; Deng, Jianqing; Liu, Min; Xue, Ya; Bao, Jizhang; Jia, Tingting; Hu, Qi; Zhang, Lichao (Frontiers in Medicine, 2025)
VV116 is an oral antiviral drug against SARS-CoV-2, known for its favorable efficacy and safety profile. But its application in patients with severe liver dysfunction has not been evaluated. Here, we report a case in which a patient with aplastic anemia and liver impairment (recovery phase of acute liver failure) was infected with SARS-CoV-2. Based on clinical trials and pharmacokinetic analysis about VV116, we initiated a reduced dose of 300 mg every 12 h on day 1, 200 mg every 12 h on days 2–5 for antiviral therapy. Finally, the patient’s viral load rapidly dropped to an undetected level, and no drug-related adverse effects were observed.